Community Empowerment in Social Capital Perspective (Study on Kalianget Salt Farmer Group in Sumenep Regency) - Yuliastina, Roos; Isyanto, Isyanto; Setiani, Puspita Pebri (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Community empowerment is an alternative development paradigm that aims to empower society and foster independence. From the perspective of social capital development, it can increase community empowerment. Social capital can increase a sense of ownership and trust within the community. A sense of trust and ownership among community members can ensure sustainable development. The research method used qualitative methods. Data collection techniques used observation and interviews. There were seven informants: four coastal residents from Karanganyar village and four from Pinggirpapas village, Kalianget subdistrict, Sumenep Regency. The results of the research showed that three dimensions of social capital, including (1) Networks or ties, (2) Trust, and (3) Values and Norms. The explanation of the three elements of social capital includes (1) Social Network, a pattern of exchange interactions based on the principle of benefit or advantage; (2) Community Trust, communities or groups unite and contribute to each other; (3) Values and Norms: general standards regarding individual behavior and attitudes related to social life in society. Contribution to Sustainable Development Goals (SDGs):SDG 11: Sustainable Cities and CommunitiesSDG 17: Partnership for the Goals